Stars-- the inside story. - World Book, Inc. (Chicago : World Book, 2010)
"An introduction to stars with information about their age, size, colors, and other characteristics. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher.
Includes bibliographical references (p. 62) and index.
Keywords: Stars -- Juvenile literature